Interpreting Inverse Magnetic Fabric in Miocene Dikes From Eastern Iceland - Trippanera, D.; Porreca, M.; Urbani, S.; Kissel, C.; Winkler, A.; Sagnotti, L.; Nazzareni, S.; Acocella, V. (Journal of Geophysical Research: Solid Earth, 2020)
International audience Anisotropy of Magnetic Susceptibility (AMS) is a valid tool to investigate magma flow direction within dikes. However, geometrically inverse magnetic fabric characterized by maximum magnetic susceptibility axis (kmax) perpendicular to the dike wall may complicate the interpretation of flow trajectories. To better understand the nature of this fabric, we present a multiscale study on 19 dikes (383 samples) in the Miocene Alftafjordur volcanic system (Iceland), where 80% of the samples show a geometrically inverse magnetic fabric. We carried out (1) AMS measurements at different magnetic fields and temperatures, along with Anisotropy of Anhysteretic Remanent Magnetization (AARM) analysis; (2) hysteresis loops and FORC diagrams; (3) thin section analysis; (4) structural fieldwork. A variable Ti-content (0.1 < x < 0.6, Fe 3-x Ti x O 4 ) titanomagnetite is the main magnetic carrier, and the contribution of the paramagnetic elongated crystals to the magnetic fabric is negligible. Single domain is not the prevailing domain state of the magnetic particles, suggesting that its occurrence cannot be the main cause for the inverse fabric. AMS analysis at different fields and temperatures along with AARM allow us to exclude any mineral phase change of the titanomagnetite across the dike. Nevertheless, kmax is parallel to a diffuse horizontal column-like fracture pattern perpendicularly oriented with respect to the dike strike. This suggests that the Ti-magnetite mineral orientation during dike cooling was affected by the fracture network progressively developing columnar basalts. This study demonstrates that the interpretation of AMS data on old and deep volcanic bodies is not straightforward and observations at different scales are required.